2021
DOI: 10.1099/mgen.0.000725
|View full text |Cite
|
Sign up to set email alerts
|

Genomic diversity of antimicrobial resistance in non-typhoidal Salmonella in Victoria, Australia

Abstract: Non-typhoidal Salmonella (NTS) is the second most common cause of foodborne bacterial gastroenteritis in Australia with antimicrobial resistance (AMR) increasing in recent years. Whole-genome sequencing (WGS) provides opportunities for in silico detection of AMR determinants. The objectives of this study were two-fold: (1) establish the utility of WGS analyses for inferring phenotypic resistance in NTS, and (2) explore clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 91 publications
4
1
1
Order By: Relevance
“…No β-lactam resistance genes were detected in two isolates (11586 and 11588) that were phenotypically resistant to ampicillin. Although not frequently observed, similar findings have been recently reported ( Sia et al., 2021 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No β-lactam resistance genes were detected in two isolates (11586 and 11588) that were phenotypically resistant to ampicillin. Although not frequently observed, similar findings have been recently reported ( Sia et al., 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…(2017) . The disagreement between genotypic and phenotypic profiles for aminoglycoside resistance as observed in isolates 11579, 11585, 11586 and 11588 from our study has been previously observed in Salmonella enterica serovars ( Cooper et al., 2020 ; Sia et al., 2021 ). The mechanisms associated with these incongruous findings should be further investigated.…”
Section: Discussioncontrasting
confidence: 70%
“…Validation of inferred phenotype against phenotypic AST data demonstrated 98.9% accuracy (95% CI 98.7-99.1%), 98.9% sensitivity (98.4-99.3) and 98.9% specificity (98.7-99.1%) overall (Table 1, Supplementary Table S5 and Figure 6). Accuracy of phenotypic inference was ≥98% for 11/13 antimicrobials (85%), with lower accuracy identified for streptomycin (95.5%, 95% CI 93.7-96.9%) and ciprofloxacin (96.8%, 95% CI 95.4-97.8%), similar to previous findings using different bioinformatic methods 25 .…”
Section: Resultssupporting
confidence: 86%
“…8%), similar to previous findings using different bioinformatic methods25 .A number of 'false positive' results were identified for streptomycin (resistant genotype [AMR genes or mutations detected], susceptible phenotype; n=30/716 (4.2%) isolates). The AMR genes detected in phenotypically susceptible isolates were also detected in non-susceptible isolates, although the non-susceptible isolates more often had >1 AMR gene (1 AMR gene, 22% phenotypically resistant; 2 or more AMR genes, 81.4% phenotypically resistant), suggesting that these AMR mechanisms had small but additive effects on phenotype.…”
supporting
confidence: 86%
“…[37][38] This has been recently proved with Carbapenemases in particular with NDM-1 metallo--lactamase producing pathogens. [39][40] However the existence of CTX-M enzymes in animals and food merchandises that are moved among different countries have proposed the likely paths for spread and dispersion. 41 Moreover this rapid dissemination has also been attributed to presence of blaCTX-M of plasmid and transposons, which confer rapid transfer of resistant elements not only within the specie but also to any bacteria it comes in contact to.…”
Section: Penetration and Globalization Of Ctx-m Enzymes All Over The ...mentioning
confidence: 99%